Will the Antarctic tardigrade Acutuncus antarcticus be able to withstand environmental stresses related to global climate change? - Ilaria Giovannini; Tiziana Altiero; Roberto Guidetti; Lorena Rebecchi (Journal of Experimental Biology, 2018)
Because conditions in continental Antarctica are highly selective and extremely hostile to life, its biota is depauperate, but well adapted to live in this region. Global climate change has the potential to impact continental Antarctic organisms because of increasing temperatures and ultraviolet radiation. This research evaluates how ongoing climate changes will affect Antarctic species, and whether Antarctic organisms will be able to adapt to the new environmental conditions. Tardigrades represent one of the main terrestrial components of Antarctic meiofauna; therefore, the pan-Antarctic tardigrade Acutuncus antarcticus was used as model to predict the fate of Antarctic meiofauna threatened by climate change. Acutuncus antarcticus individuals tolerate events of desiccation, increased emperature and UV radiation. Both hydrated and desiccated animals tolerate increases in UV radiation, even though the desiccated animals are more resistant. Nevertheless, the survivorship of hydrated and desiccated animals is negatively affected by the combination of temperature and UV radiation, with the hydrated animals being more tolerant than desiccated animals. Finally, UV radiation has a negative impact on the life history traits of successive generations of A. antarcticus, causing an increase in egg reabsorption and teratological events. In the long run, A. antarcticus could be at risk of population reductions or even extinction. Nevertheless, because the changes in global climate will proceed gradually and an overlapping of temperature and UV increase could be limited in time, A. antarcticus, as well as many other Antarctic organisms, could have the potential to overcome global warming stresses, and/or the time and capability to adapt to the new environmental conditions.